Early in vivo osteogenic and inflammatory response of 3D printed polycaprolactone/carbon nanotube/hydroxyapatite/tricalcium phosphate composite scaffolds - Nalesso, Paulo Roberto Lopes (2023)
The development of advanced biomaterials and manufacturing processes to fabricate biologically and mechanically appropriate scaffolds for bone tissue is a significant challenge. Polycaprolactone (PCL) is a biocompatible and degradable polymer used in bone tissue engineering, but it lacks biofunctionalization. Bioceramics, such as hydroxyapatite (HA) and β tricalcium phosphate (β-TCP), which are similar chemically to native bone, can facilitate both osteointegration and osteoinduction whilst improving the biomechanics of a scaffold. Carbon nanotubes (CNTs) display exceptional electrical conductivity and mechanical properties. A major limitation is the understanding of how PCL-based scaffolds containing HA, TCP, and CNTs behave in vivo in a bone regeneration model. The objective of this study was to evaluate the use of three-dimensional (3D) printed PCL-based composite scaffolds containing CNTs, HA, and β-TCP during the initial osteogenic and inflammatory response phase in a critical bone defect rat model. Gene expression related to early osteogenesis, the inflammatory phase, and tissue formation was evaluated using quantitative real-time PCR (RT-qPCR). Tissue formation and mineralization were assessed by histomorphometry. The CNT+HA/TCP group presented higher expression of osteogenic genes after seven days. The CNT+HA and CNT+TCP groups stimulated higher gene expression for tissue formation and mineralization, and pro- and anti-inflammatory genes after 14 and 30 days. Moreover, the CNT+TCP and CNT+HA/TCP groups showed higher gene expressions related to M1 macrophages. The association of CNTs with ceramics at 10wt% (CNT+HA/TCP) showed lower expressions of inflammatory genes and higher osteogenic, presenting a positive impact and balanced cell signaling for early bone formation. The association of CNTs with both ceramics promoted a minor inflammatory response and faster bone tissue formation.